Environmental planning for sustainable development of hill areas : a case study approach - Maithani, B. P. (New Delhi, India : Mittal Publications, 1992)
Study conducted in Nadaun Tehsil, Himachal Pradesh.
Includes bibliographical references and index
Keywords: Land use, Rural -- Case studies. -- Planning -- India; Hill farming -- Case studies. -- Planning -- India